Assessing the Role of Motivation and Work Discipline in Enhancing Outsourced Employee Performance - Dery Dwantara; Dedi Hadian; Aan Hardiyana (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2026)
This research addresses the significant influence of work motivation and discipline on employee performance at a human resource provider. The main aim is to determine which of these factors exerts the strongest impact on performance. To achieve this, the study employs descriptive and verification methods, gathering data from 40 employees through a targeted questionnaire. The findings reveal that the motivation variable directly affects performance, while it also has an indirect impact through the relationship with work discipline. Conversely, work discipline similarly demonstrates both a direct influence and an indirect effect via motivation. The analysis indicates that motivation and work discipline together account for a substantial portion of the variance in employee performance, while other unexamined factors account for the remainder. The novelty of this study lies in its combined approach to assessing these variables in an outsourcing context, offering insights that could enhance employee management strategies. The implications suggest that management should actively work to sustain and improve motivation and discipline levels to boost performance and foster a productive work environment.